Velocity Distributions in a Gas-Gun Microparticle Accelerator - Barrios Borregales, Siria Karely del Carmen (2022)
Here, we build and characterize a single-stage gas-gun microparticle accelerator, where a pressurized gas expands and launches particles on a target. The microparticles in the range of 60-250 μm are accelerated by the expansion of pressurized nitrogen. By using a high-speed camera, we study how the velocity distribution of accelerated particles is modified by particle size, pressure in the gas reservoir, valve's opening time, and diaphragm's thickness and composition. We employ this microparticle accelerator to study the impact of glass particles with diameters of (69 ± 6) μm accelerated at moderate velocities ∼(10-25) m/s, using films of poly-dimethylsiloxane as targets.